Peningkatan Bernalar Kritis Peserta Didik Melalui Pendekatan Problem Based Learning Fase F Kelas XI SMKN 1 Sokan - Jultiram Jultiram (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This research is motivated by the low level of critical thinking skills among Grade XI students at SMKN 1 Sokan, which has negatively impacted their learning outcomes in Catholic Religious Education. The aim of this study is to enhance students’ critical reasoning abilities through the implementation of Problem-Based Learning (PBL) Phase F, supported by audiovisual media. The method employed is Classroom Action Research (CAR), conducted over two cycles, utilizing data collection techniques such as observation, interviews, documentation, and learning outcome assessments. The findings indicate that the integration of PBL and audiovisual media significantly improves students’ active participation, analytical skills, and ability to formulate logical solutions. Audiovisual media has proven effective in facilitating concrete understanding of contextual materials. This approach is recommended as an instructional strategy for fostering critical thinking skills in Catholic Religious Education.